International Branding - Hsieh, Heng Hui, Berry (2009)
Inspired by the reluctance of SME of invest in brand in internationalization plan, the author aims at finding the driving factors of an international brand. In spite of the traditional approach considering competitive advantages and market competition theory, the author looks at the managerial factors and industrial environment variables to a useful mind of thoughts of international brand strategy. A well-developed literature review emphasized on the inceptive stage of international has been presented, namely, unlike traditional brand strategy that generally focusing on the resource side of a firm, this report put more effort on the impetus influencing a firm to prefer/ disregard international brand strategy by a qualitative research. Also, the relevance of commitment in international branding with reference to SMEs is explained whilst elaborating on what drives commitment to international branding. Factors that influence branding from a global angle are discussed with respect to framing a discussion on strategic perspectives of branding. These discussions form the backbone of brand strategy by leading us to decide whether branding is driven by endogenous and exogenous factors, or is just a product of an SME’s functionality. It has been indicated that branding nevertheless, has to prove beneficial to the international firm’s performance. Furthermore, 3 case studies associated with international brand challenges that almost every company will face during internationalization will also be discussed by consolidating all the points made in order to suggest a more down-to-earth and pragmatic international branding solution. The paper concludes by saying mainly that an SME’s international brand can be established successfully by aligning self-advantages with brand strategy. The Executive's personal ambition could also strongly influence establishment of a brand. Brand is also said to be as the result of the country’s strategic competition or being a compromising result of foreign market's uniqueness of social and culture aspects. The author also emphasizes that a company, irrespective of its product-life-cycle can use guidelines such as Keller’s Customer-based-Brand Equity Model (CBBE) model for successfully branding itself.